Electronic-Module Range of Motion on Family Caregivers in Increasing Muscle Strength in Stroke Sufferers - Miftafu Darussalam; Ferianto Ferianto (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
The level of dependence of stroke sufferers on family caregivers will increase along with the complications experienced by stroke sufferers. The role of the family is to contribute to the rehabilitation process at home in the form of physical and psychosocial benefits. One effort can be made by providing Range of Motion exercises to stroke sufferers. Different family backgrounds and the importance of empowering the role of family caregivers require media that is informative and can be accessed anywhere. This study aimed to test the effectiveness of the Electronic-Module Range of Motion (E-ROM) for family caregivers in carrying out ROM and assessing muscle strength in stroke sufferers—a quasi-experimental research design with a pretest-posttest control group design. Research analysis used the Wilcoxon Test and Mann-Whitney Test. The sample consisted of 46 respondents for the treatment group and control group. The intervention providing E-Module ROM exercises was given to family caregivers, and assistance was provided. ROM exercises for stroke sufferers are carried out twice daily for two weeks. Health education with Electronic-Module Range of Motion (E-ROM) can increase muscle strength in stroke sufferers.